Serological Immunoassay for Hansen’s Disease Diagnosis and Monitoring Treatment: Anti-Mce1A Antibody Response Among Hansen’s Disease Patients and Their Household Contacts in Northeastern Brazil - Lima, Filipe Rocha; Filho, Fred Bernardes; Antunes, Vanderson Mayron Granemann; Santana, Jaci Maria; de Almeida, Regina Coeli Palma; Toro, Diana Mota; Bragagnollo, Vinicius Fozatti; Manso, Gabriel Martins da Costa; de Paula, Natália Aparecida; Alves, Eliracema Silva; Riley, Lee W.; Arruda, Sérgio; et al. (Frontiers in Medicine, 2022)
Hansen’s disease (HD) is an ancient disease, but more than 200,000 new cases were reported worldwide in 2019. Currently, there are not many satisfactory immunoassay methods for its diagnosis. We evaluated antibodies against Mce1A as a promising new serological biomarker. We collected plasma from new cases, contacts, and endemic controls in the city of Parnaíba and treated patients at Carpina, a former HD colony in Piauí state, northeastern Brazil. Receiver operating characteristic (ROC) curves were used to assess the assay thresholds, specificity and sensitivity of the IgA, IgM, and IgG antibodies against α-Mce1A by indirect ELISA and compared it with IgM anti-PGL-I and molecular diagnosis by qPCR. Venn diagrams were generated to represent the overlap in the antibody positivity pattern. Multivariate analysis was performed to assess the potential predictor of antibodies for the outcome of having an HD diagnosis. IgA and IgG were positive in 92.3% and 84% of patients, respectively. IgM was negative for all treated patients. IgG had a sensitivity and specificity of 94.7% and 100%, respectively. IgM-positive individuals had a 3.6 chance of being diagnosed with HD [OR=3.6 (95% CI=1.1-11.6); p=0.028], while IgA-positive individuals had a 2.3 chance [OR=2.3 (95% CI=1.2-4.3); p=0.005] compared to endemic controls. We found that the Mce1A antibody profile can be an excellent diagnostic method of HD. IgA is an ideal biomarker for confirming contact with the bacillus. IgM has potential in the detection of active disease. IgG antibodies confirm the performance of these serological markers in diagnosis and therapeutic follow-up.